2014
DOI: 10.1001/jama.2014.10707
|View full text |Cite
|
Sign up to set email alerts
|

Use of and Mortality After Bilateral Mastectomy Compared With Other Surgical Treatments for Breast Cancer in California, 1998-2011

Abstract: IMPORTANCE Bilateral mastectomy is increasingly used to treat unilateral breast cancer. Because it may have medical and psychosocial complications, a better understanding of its use and outcomes is essential to optimizing cancer care. OBJECTIVE To compare use of and mortality after bilateral mastectomy, breast-conserving therapy with radiation, and unilateral mastectomy. DESIGN, SETTING, AND PARTICIPANTS Observational cohort study within the population-based California Cancer Registry; participants were wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
191
2
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(208 citation statements)
references
References 37 publications
(56 reference statements)
6
191
2
4
Order By: Relevance
“…Analysis of data from the California Tumor Registry shed additional light on this issue [6]. These data suggested that trends in the utilization of CPM are closely linked to age at…”
Section: Abstract Breast Cancer Contralateral Prophylactic Mastectomentioning
confidence: 98%
See 2 more Smart Citations
“…Analysis of data from the California Tumor Registry shed additional light on this issue [6]. These data suggested that trends in the utilization of CPM are closely linked to age at…”
Section: Abstract Breast Cancer Contralateral Prophylactic Mastectomentioning
confidence: 98%
“…Yet, the overall rate of mastectomy in the United States decreased from 40.8 % in 2000 to 37 % in 2006 (when mastectomy rates for invasive breast cancers and DCIS were considered together), indicating that lumpectomy was still the preferred option [4]. Taken together, these results indicate that more women were choosing lumpectomy in the United States, but among those who chose mastectomy, CPM was increasingly becoming the preferred option.Analysis of data from the California Tumor Registry shed additional light on this issue [6]. These data suggested that trends in the utilization of CPM are closely linked to age at…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Хотя наблюдалось небольшое преимущество в показателе выживаемости [33], не была доступна информация о статусе BRCA, который, как известно, является показанием к профилактической мастэктомии и маркером получения пользы от такой операции [34]. За последние 2 десятилетия в США отмечается увеличение частоты выполнения контралатеральных профилактических мастэктомий, в частности у женщин моложе 40 лет [35]. В Европе такая тенденция менее выражена [36,37].…”
Section: хирургическое лечениеunclassified
“…The number of patients undergoing both prophylactic and therapeutic mastectomy has grown exponentially in the last decade due to the increased availability of genetic testing and breast cancer surveillance (1)(2)(3)(4). For post-mastectomy patients, autologous breast reconstruction has shown to significantly improve their psychosexual well-being and has subsequently become an integral part of the breast cancer treatment (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%